Preparation of 3D structure high performance Ba0·5Sr0·5Fe0·8Cu0·2O3-δ nanofiber SOFC cathode material by low-temperature calcination method. (11th February 2021) - Bai, Jinghe; Han, Zhiying; Lv, Bu; Chen, Xu; Zhu, Xiaofei; Zhou, Defeng
Abstract: The electrospinning and sol-gel methods are used to prepare a Ba0·5 Sr0·5 Fe0·8 Cu0·2 O3-δ (BSFC) cathode material with good chemical compatibility with the traditional electrolyte Ce0.8 Gd0.2 O2−δ (GDC). Systematic experiments are performed to investigate the effect of sintering temperature on BSFC fibers microstructure, morphology and electrochemical properties. The results show that the three dimensional (3D) BSFC-F800 prepared by the low-temperature calcination method (800 °C) has a well-organized porous structure and larger specific surface area and porosity. In addition, the fibers are connected to each other to form a continuous electrode path, which provides an uninterrupted channel for charge transmission, and the low-temperature calcination can efficiently reduce the surface Sr segregation and increase ORR activity. At 700 °C, the 3D nanofiber cathode material BSFC-F800 has lower area specific resistance (ASR = 0.128 Ω cm 2 ) and higher peak power density (PPD = 0.51 W cm −2 ). The voltage decay rate in the 100 h long-term stability test is only 0.0342% h −1 . Graphical abstract: Changes of morphology and electrical properties of Ba0·5 Sr0·5 Fe0·8 Cu0·2 O3-δ fibers prepared by electrostatic spinning at different calcination temperatures. After calcination at low temperature, a hollow 3D fiber cathode with higher specific surface area is obtained. With the increase of temperature, grain expands, fiber diameter increases, and hollow structure becomes solid structure. As the temperature continues to rise, the fibers agglomerate together, seriously damaging the specific surface area and porosity of Ba0·5 Sr0·5 Fe0·8 Cu0·2 O3-δ fibers. Image 1 Highlights: B-site Cu doped Fe-based Ba0·5 Sr0·5 Fe0·8 Cu0·2 O3-δ fiber cathode material. 3D structure fiber was prepared by low temperature method. Low temperature sintering can effectively reduce the surface Sr segregation. 3D structure Ba0·5 Sr0·5 Fe0·8 Cu0·2 O3-δ has excellent performance.